Economic Perspective, Cultural Perspectives, and Sharia Perspective in Revenue Sharing For Village Economic Empowerment (Case Study on Gaduh Culture in East Java) - Moch. Khoirul Anwar; Hariyati Hariyati (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
Theoretically, revenue is one of local wisdom community empowerment models which is effective nowadays. This model is based on potential and social fabric conditions of the local community. The study aims to analyze the influence of the economic perspectives, cultural perspective and sharia perspective on revenue of society’s income in East Java.This study uses a mixed methods study, with a qualitative and quantitative approach. The population and samples are the society in Blitar, Jombang, and Madiun. The result of the qualitative analysis showed that there are three (3) models of implementasion in cow-calf lease agreement (gaduh) and share farming (paron) system. The first model implements profit sharing system by taking maintenance cost into account. The second model implements sharing system as well but it takes farming workers in the deficit of profit cost into account. The revenue that is based on profit sharing is still in 50:50. While the third model uses revenue sharing system without taking administration and workers cost as the cost component. However, the revenue proportion becomes 75:25. Those models are reviewed from shariah perspective, economic perspective and cultural perspective. From quantitative analysis showed that economic perspective has bigger influence.Keywords: Economic Perspectives, Mixed Method, Profit Sharing, Revenue, Shariah Perspective